Lithostratigraphic column between Nevesinje and Ljubinje including highlights of the karst area characteristics (Southeastern Bosnia & Herzegovina) - Bašagić, Mirza (Geologija, 2003)
The area between Nevesinje and Ljubinje in Eastern Herzegovina is a part of the Dinaric massif, where Masozoic carbonated platform is almost completely preserved. There are also Palaeogene sediments in the structure of the area, but they are considerably less preserved. The purpose of this paper is to provide information on lithofacies, tectonic structures and karst characteristics.
Keywords: Bosna in Hercegovina, vzhodna; Dinaridi; karbonatne kamnine; karst; kenozoik; kras (geologija); kraški pojavi; litostratigrafija; mezozoik; sedimentne kamnine